The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/17512780701768527
|View full text |Cite
|
Sign up to set email alerts
|

Journalism and Blogging

Abstract: Adopting a systems framework from the sociology of occupations, this study proposes a model to explain the vulnerabilities of journalism in the face of challenges from blogging, and the conditions under which journalists are likely to change their practices to address these vulnerabilities. A test of this model shows that editors' awareness of local blogging activity corresponds to increased use of blogs as sources, discussion of blogs in planning meetings and adoption of the blogging form on news websites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 27 publications
(18 reference statements)
0
8
0
1
Order By: Relevance
“…Although multimedia journalism requires journalists to alter their practices to accommodate new tools, participatory journalism has necessitated an articulation of what journalists do that those outside the newsroom do not (Lowrey & Mackay, 2008). Their response to this existential question has centered on professional values and normative standards, with journalists arguing that commitment to such norms as accuracy and impartiality sets them apart (Singer, 2010).…”
Section: Diffusion and Newsroom Changementioning
confidence: 99%
“…Although multimedia journalism requires journalists to alter their practices to accommodate new tools, participatory journalism has necessitated an articulation of what journalists do that those outside the newsroom do not (Lowrey & Mackay, 2008). Their response to this existential question has centered on professional values and normative standards, with journalists arguing that commitment to such norms as accuracy and impartiality sets them apart (Singer, 2010).…”
Section: Diffusion and Newsroom Changementioning
confidence: 99%
“…Some research reports that media workers maintain old values in the midst of digital changes (O'Sullivan and Heinonen, 2008) and actively devalue user-generated content (Lewis et al, 2009). Still other scholars have suggested that blogs alter reporters' conceptions of immediacy, interactivity and transparency (Bivens, 2008) and influence newsroom conversations and sourcing practices (Lowrey and Mackay, 2008). This research explored what online contributors think about their role as information producers, as well as how the journalists perceive that role.…”
Section: New Members and Citizen Journalistsmentioning
confidence: 99%
“…Opinions differ about whether merely offering these technologies to the audience really leads to an organisational change, even if the tools apparently fulfil an existing public need. Some contend that external forces leading to changes within journalism are almost automatically accepted by journalists as a means of self-preservation (Lowrey and Mackey, 2008). Others argue that organisational change will not take place unless the policy makers in the newsroom actively encourage it*something that is usually not quite their habit (Sigelman, 1973).…”
Section: The Internet's Influencementioning
confidence: 99%